Legal Implications of the Transfer of a Testamentary Grant's Object to Another Person by the Testator - Putri Thania Dewinta; Abdul Madjid; Dyah Widhiawati (Faculty of Law, University of Jember, Indonesia, 2025)
This research is motivated by a lawsuit filed by Imelda Sanny Chandra (Plaintiff) against her grandmother, Mrs. Tinningrum Tjandra (Defendant I), regarding the transfer of a testamentary grant object—a plot of land and a building in Surabaya—to Mrs. Koesoemo Dewi Raharjo (Defendant II) through a sale and purchase agreement. The Plaintiff argues that the object rightfully belongs to her based on Testamentary Grant Deed Number 119, which was executed by Defendant I before a Notary in Jakarta. One of the clauses in the deed states that the object would be transferred to the Plaintiff upon reaching the age of 30. Currently, the Plaintiff is 32 years old and intends to reclaim the testamentary grant object. Ruling Number 3258 K/Pdt/2023 in conjunction with Ruling Number 1270/Pdt.G/2021/PN.Sby declared the Testamentary Grant Deed valid and annulled the agreement between Defendant I and Defendant II. However, in the context of Article 958 of the Indonesian Civil Code concerning the execution of testamentary grants and Article 996 of the Civil Code regarding the revocation of testamentary grants, this study aims to analyze the legal nature of testamentary grants and the juridical implications of the grantor transferring the object to another party. The goal is to provide legal certainty regarding the testamentary grant deed, the sale and purchase binding deed, the power of attorney to sell, and the sale and purchase deed issued in connection with this ruling. This research employs a normative juridical method with a legislative approach, a teleological approach, and a case approach. The data sources include primary, secondary, and tertiary legal materials. The analysis is conducted through grammatical and systematic interpretation.